Drought impact on rural economy of Rayalaseema a Case Study on 6 Villages Of Kadapa District (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
The share of agriculture sector in the country's GDP is lagging behind with respect to other sectors; it can be witnessed that the same trend is continuing in the annual income of the families which are depending on that sector, compared to the annual income of the families of the other sectors. If such trend continues, the future of the majority of people who eke out their livelihood from the agriculture sector would be gloomy and dismal. Agriculture is the main source of income for both the farming community and labour community in the district. But the district is characterized by continuous droughts, low rain fall, inadequate irrigation facilities, etc. These are the reasons for the low levels of income. There are various reasons for that to happen, primarily due to drought and the development model that the country has chosen and due to the government neoliberal policies. This paper analyzed the drought impact on rural economy and rural households’ incomes Kadapa district is one of the 13 districts in the State of Andhra Pradesh. Kadapa district lies in the region of Rayalaseema, in the state of Andhra Pradesh.